2015
DOI: 10.9734/bjemt/2015/17849
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model of the Price Dispersion of Homogeneous Goods

Abstract: Presented is an analytic microeconomic model of the temporal price dispersion of homogeneous goods in polypoly markets. This new approach is based on the idea that the price dispersion has its origin in the dynamics of the purchase process. The price dispersion is determined by the chance that demanded and supplied product units meet in a given price interval. It can be characterized by a fat-tailed Laplace distribution for short and by a lognormal distribution for long time horizons. Taking random temporal va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 17 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…where the functions x(p,t) and z(p,t) have maximum overlap [10]. The supply function z(p,t) is governed by the costs per unit for the generation of electricity, which depends on the applied production technology.…”
Section: Discussionmentioning
confidence: 99%
“…where the functions x(p,t) and z(p,t) have maximum overlap [10]. The supply function z(p,t) is governed by the costs per unit for the generation of electricity, which depends on the applied production technology.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that this process can be described by a Fisher-Pry law of the unit sales market shares. As established in a previous work the price dynamics of homogeneous goods can be regarded as a meeting process of demanded (required) with supplied (available) product units generating a price dispersion of the form of a Laplace distribution [20,21]. The mean price of this distribution declines for homogenous goods according to a logistic law for the case of a fast growing supply [18,19].…”
Section: Introductionmentioning
confidence: 93%
“…In order to establish the price evolution of the i-th generation we introduce the number of demanded and supplied units x i (p,t) and z i (p,t) as accumulated functions over the price p [21]. Generalizing Eq.…”
Section: Price Evolution Of a Homogeneous Generationmentioning
confidence: 99%
See 2 more Smart Citations